Walking with the Unicorn social organization and material culture in ancient South Asia : Jonathha Mark Kenoyer felicitation volume - Frenez, Dennys; Jamison, Gregg; Law, Randall W.; Vidale, Massimo 1956-; Meadow, Richard H. (Archaeopress Archaeology, 2018)
This volume, a compilation of original papers written to celebrate the outstanding contributions of Jonathan Mark Kenoyer to the archaeology of South Asia over the past 40 years, highlights recent developments in the archaeological research of ancient South Asia, with specific reference to the Indus Civilisation
Keywords: Kenoyer, Jonathan Mark -- 1952-; Excavations (Archaeology) / South Asia; Sachkultur; Bronzezeit; Gesellschaft; Harappakultur; South Asia / Antiquities; South Asia / Civilization; Südasien; Festschrift; Aufsatzsammlung